THE PHASE BOUNDARY BETWEEN WADSLEYITE AND RINGWOODITE IN MG2SIO4 DETERMINED BY IN SITU X-RAY DIFFRACTION - Inoue T.; Irifune T.; Higo Y.; Sanehira T.; Sueda Y.; Yamada A.; Shinmei T.; Yamazaki D.; Ando J.; Funakoshi K.; Utsumi W. (My University, 2006)
The phase boundary between wadsleyite and ringwoodite in Mg2SiO4 has been determined in situ using a multi-anvil apparatus and synchrotron X-rays radiation at SPring-8. In spite of the similar X-ray diffraction profiles of these high-pressure phases with closely related structures, we were able to identify the occurrence of the mutual phase transformations based on the change in the difference profile by utilizing a newly introduced press-oscillation system. The boundary was located at ~18.9 GPa and 1,400°C when we used Shim’s gold pressure scale (Shim et al. in Earth Planet Sci Lett 203:729–739, 2002), which was slightly (~0.8 GPa) lower than the pressure as determined from the quench experiments of Katsura and Ito (J Geophys Res 94:15663–15670, 1989). Although it was difficult to constrain the Clapeyron slope based solely on the present data due to the kinetic problem, the phase boundary [P (GPa)=13.1+4.11×10−3×T (K)] calculated by a combination of a P–T position well constrained by the present experiment and the calorimetric data of Akaogi et al. (J Geophys Res 94:15671–15685, 1989) reasonably explains all the present data within the experimental error. When we used Anderson’s gold pressure scale (Anderson et al. in J Appl Phys 65:1535–1543, 1989), our phase boundary was located in ~18.1 GPa and 1,400°C, and the extrapolation boundary was consistent with that of Kuroda et al. (Phys Chem Miner 27:523–532, 2000), which was determined at high temperature (1,800–2,000°C) using a calibration based on the same pressure scale. Our new phase boundary is marginally consistent with that of Suzuki et al. (Geophys Res Lett 27:803–806, 2000) based on in situ X-ray experiments at lower temperatures (<1,000°C) using Brown’s and Decker’s NaCl pressure scales.
Keywords: WADSLEYITE; RINGWOODITE; PHASE TRANSFORMATION; HIGH PRESSURE; IN SITU X-RAY DIFFRACTION